Biological fate of food nanoemulsions and the nutrients they carry – internalisation, transport and cytotoxicity of edible nanoemulsions in Caco-2 intestinal cells. Issue 64 (16th August 2017) - Wooster, Tim J.; Moore, Sean C.; Chen, Wei; Andrews, Helen; Addepalli, Rama; Seymour, Robert B.; Osborne, Simone A.
Abstract : Internalisation of edible food nanoemulsions by CaCo-2 intestinal cells. The structure of edible nanoemulsions increases five times upon incorporation of reactive/ROS producing nutrients/APIs. Abstract : Edible nanoemulsions are promising delivery systems with the potential to enhance nutrient/drug solubilisation, digestibility, bioavailability and potentially facilitate direct cellular uptake. However, the high potential of edible nanoparticles has also led to concerns about their biological fate and whether these nanoparticles or the active ingredients they carry pose (new) toxicological risks. Here we outline the development of new sub 50 nm edible nanoemulsions that allow us to probe the duality of enhanced nutrient solubilisation and bioavailability with potential toxicological side effects. The toxicity and biological fate of the edible nanoemulsions was investigated using Caco-2 cells to facilitate cell viability assays, transport of nanoemulsions across an in vitro intestinal model and internalisation visualised by confocal microscopy. These experiments demonstrate that edible nanoemulsion toxicity is not just a function of surfactant composition, but more critically a synergistic effect between surfactants and their physical location. Critically the presence of reactive ingredients (β-carotene) leads to a dramatic increase in nanoemulsion toxicity that may counteract the benefits associated with enhanced solubilisation/cellular uptake. Such research into the biological fate of edible food nanoemulsions and the nutrients they carry is important not only because nanotechnology in food is an emotive topic, but also because these insights may inform public policy decisions.